Erythrocyte Malondialdehyde and Glutathione Levels in Vitiligo Patients - Shin, Jung Won; Nam, Kyung Mi; Choi, Hye Ryung; Huh, Sun Young; Kim, Shin Woo; Youn, Sang Woong; Huh, Chang Hun; Park, Kyoung Chan (Annals of dermatology, 2010)
Vitiligo is an acquired and progressive hypomelanotic disease that manifests as circumscribed depigmented patches on the skin. Although the precise mechanism remains to be elucidated, an imbalance of the oxidant/antioxidant system has been proposed as an important etiologic mechanism. The objective of this study was to evaluate the oxidant/antioxidant status of vitiligo patients at the erythrocyte level. Fifty-three vitiligo patients and 65 phototype-, age-, and sex-matched healthy controls were included in this study. Blood samples were collected from all subjects, and all patients were instructed to answer a questionnaire. Erythrocyte levels of malondialdehyde (MDA) and glutathione (GSH) were measured. All patients were told to answer a questionnaire regarding their habitual behavior, including frequency of smoking and type of diet. We observed significantly lower levels of GSH in vitiligo patients, but the levels of MDA did not differ between patients and controls. Vitiligo patients who smoked showed significantly lower GSH levels compared to non-smoking patients, but the levels of MDA were unchanged between the 2 groups. From our results, we conclude that reduced erythrocytic or systemic GSH levels constitute a distinctive feature in vitiligo patients regardless of disease activity.